(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The paper discusses the typology of corporate social responsibility strategies (CSR), depending on the degree of response to stakeholders’ requests. It has been determined that proactive CSR strategy includes voluntary business initiatives going beyond legislation limits and being aimed at meeting the needs of a wide range of stakeholders. It has been proved that the use of the proactive CSR strategy ensures achievement and support of long-term competitive advantages through the complex of value-oriented actions. The mechanism of influence of proactive socially responsible practices on the formation of competitive advantages from the standpoint of resource-based, dynamic resource-based and relational view has been considered. It has been proved that within the framework of relational view the success of the companies’ proactive actions towards stakeholders can be explained by the relational potential growth. The economic, social and environmental aspects of proactive CSR strategy have been described.